210Po-210Pb Disequilibrium in the Western North Pacific Ocean: Particle Cycling and POC Export - Zhong, Qiangqiang; Yu, Tao; Lin, Hui; Lin, Jing; Ji, Jianda; Ni, Jialin; Du, Jinzhou; Huang, Dekun (Frontiers in Marine Science, 2021)
Estimating the particulate organic carbon (POC) export flux from the upper ocean is fundamental for understanding the efficiency of the biological carbon pump driven by sinking particles in the oceans. The downward POC flux from the surface ocean based on 210Po-210Pb disequilibria in seawater samples from the western North Pacific Ocean (w-NPO) was measured in the early summer (May-June) of 2018. All the profiles showed a large 210Po deficiency relative to 210Pb in the euphotic zone (0–150 m), while this 210Po deficiency vanished below ∼500 m (with 210Po/210Pb ∼1 or > 1). A one-dimensional steady-state irreversible scavenging model was used to quantify the scavenging and removal fluxes of 210Po and 210Pb in the euphotic zone of the w-NPO. In the upper ocean (0–150 m), dissolved 210Po (D-Po) was scavenged into particles with a residence time of 0.6–5.5 year, and the 210Po export flux out of the euphotic zone was estimated as (0.33–3.49) × 104 dpm/m2/year, resulting in a wide range of particulate 210Po (P-Po) residence times (83–921 days). However, in the deep ocean (150–1,000 m), 210Po was transferred from the particulate phase to the dissolved phase. Using an integrated POC inventory and the P-Po residence times (Eppley model) in the w-NPO euphotic zone, the POC export fluxes (mmol C/m2/d) varied from 0.6 ± 0.2 to 8.8 ± 0.4. In comparison, applying the POC/210Po ratio of all (>0.45 μm) particles to 210Po export flux (Buesseler model), the obtained POC export fluxes (mmol C/m2/d) ranged from 0.7 ± 0.1 to 8.6 ± 0.8. Both Buesseler and Eppley methods showed enhanced POC export fluxes at stations near the continental shelf (i.e., Luzon Strait and the Oyashio-Kuroshio mixing region). The Eppley model-based 210Po-derived POC fluxes agreed well with the Buesseler model-based fluxes, indicating that both models are suitable for assessing POC fluxes in the w-NPO. The POC export efficiency was < 15%, suggesting a moderate biological carbon pump efficiency in the w-NPO. These low export efficiencies may be associated with the dominance of smaller particles and the processes of degradation and subsequent remineralization of these small particles in the euphotic zone of oligotrophic regions in the w-NPO.